Oil and Gas Conference. Day 1. Tape 04. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Introduction (George Lee); Keynote speaker Ian Clarke (Shetland Islands experience, Advice for Nfld.).